Combined electrical and electrochemical-thermal model of parallel connected large format pouch cells. (April 2019) - Hosseinzadeh, Elham; Marco, James; Jennings, Paul
Highlights: A 1D electrochemical-thermal model of a large format 53 Ah pouch cell is developed. The cell model is coupled with an electrical circuit model of the ESS within Matlab. The cell closest to the ESS terminals can reach a high temperature very rapidly. High/faulty interconnect resistance can cause excessive temperatures to be generated. Large format cells, connected in parallel, may increase the risk of thermal runaway. Abstract: Variation in energy capacity and resistance of cells connected in parallel can degrade the overall performance of the energy storage system (ESS). Such variations can lead to significant individual differences in battery load current, state of charge (SOC) and heat generation. An experimentally validated 1D electrochemical-thermal model of a large format 53 Ah pouch cell is employed to underpin the performance evaluation of parallel connected cells within the context of a complete ESS. The cell model, developed within COMSOL Multiphysics is coupled with an electrical circuit model of the ESS within Matlab. Results are presented that quantify cell-to-cell differences in load current and heat generation as the length of the parallel connection and value of the cell interconnection resistance is varied. The results highlight that variations in cell depth of discharge and the occurrence of temperature gradients across the parallel connection increases at higher load currents and interconnect resistances. The impact is amplified as the length of the parallel connection increases which will accelerate cell ageing and, if unmanaged, may present safety concerns.